Pelatihan Bahasa Inggris Bagi Anak Putus Sekolah Di Otista - Sunarti; Rani Herning Puspita (Journal of Empowerment and Community Service (JECSR), 2022)
Learning is the obligation of every individual. English is a compulsory subject for elementary school to high school students. English is required not only as a fulfillment of mastery learning in schools but also future necessities in facing the era of globalization. The current pandemic situation requires children to study online at home and this is not easy for some people. The impact of the pandemic is comprehensive. Not a few children drop out of school due to their inability to receive lessons or the absence of online learning support facilities and furthermore economic factors that do require children not to be able to continue their education formally. The service team took the initiative to carry out service in locations where there were indeed children who had dropped out of school both before and after the pandemic occurred. This service is in the form of face-to-face English language training by implementing health protocols on Jalan Otto Iskandardinata or well-known as Otista. This service aims to train children with basic knowledge of communicating English and provide an understanding of the importance of education for the future.